(1012) Workshop of: Human Settlements in New Lands: Their Design and Development :Means of Implementing the Design: Organization Administration ورشة عمل: التوطين البشرى للسكان النازحين فى الأراضي الجديدة: تصميمها وتطويرها: وسائل تنفيذ التصميم: الإدارة التنظيمية - Wafik Ashraf Hassona. (INP., 2020)
The success of human resettlement projects depends on selecting an appropriate organizational model that aligns with project objectives while optimizing costs. This paper explores the key factors influencing the choice of organizational structures for resettlement initiatives, emphasizing the importance of settler participation in project management. Additionally, it examines the administrative frameworks necessary to support and operate the selected model effectively. By analyzing different approaches, this study provides insights into designing resettlement programs that enhance efficiency, sustainability, and community involvement, ultimately contributing to better outcomes for displaced populations.